Study of gender difference of opportunistic infections in AIDS patients - Sudhir Mourya; Bushra Khanam; Shivank Shrivastava; Ajay Kumar Singh (International Journal of Medical Research and Review, 2014)
Introduction: Concerns about sex-based differences in the course of HIV infection were expressed early in the epidemic. Women appeared to have more rapid progression of illness than men and to present with a different constellation of opportunistic infections than men. Conducting sex comparisons within research studies is important to delineate sex differences or similarities.Material & Methods: A prospective cohort study involving HIV infected patients scheduled to start ART, in which 156 male, 82 female and 1 transgender was undertaken to compare the gender difference in age distribution, marital status, presenting symptoms .Structured questionnaires and patients file review were used to collect. data through history, physical ex:amination and laboratory investigations. Gender differences were assessed using chi-square test for categorical data.Results: In the study population 239 patients who fulfilled NACO guidelines for AIDS were included, 156 men and 82 women. Fever was the commonest presenting symptom (57.32%) in both males and females, 61.53% of males and 48.78% females presented with fever. The most frequent AIDS Defining Infections were tuberculosis (42.25%) and candidiasis (22.6%). Pulmonary Tuberculosis, Tubercular meningitis were significantly higher in males compared to females. Herpes simplex (P value 0.007) and non specific dermatitis showed statistically significantly higher in females compared to males in occurrence rate.Conclusion: Evaluation of differences between human immunodeficiency virus (HIV)-infected men and women in antiretroviral therapy (ART) enrollment characteristics and outcomes might identify opportunities to improve ART program, patient outcomes and prevention impact. We studied gender differences in opportunistic infections in AIDS patient.